Properties of low density polyethylen/natural rubber/chemical modified water hyacinth fibers (Eichhornia Crassipes) composites - Tan, Soo Jin (School of Materials Engineering, 2013)
The natural fiber composites of low density polyethylene (LDPE)/natural rubber (NR)/water hyacinth fibers (WHF) were studied.